Do free trade agreements promote sneaky protectionism? A classical liberal perspective - Jürgen Wandel (International Journal of Management and Economics, 2019)
A neglected aspect of regional trade agreements (RTAs) is their protectionist potential. In times of a stagnating World Trade Organization (WTO), growing economic nationalism and skepticism about the merits of free trade and trade agreements, the paper examines to what extent recently signed RTAs really promote genuine free trade or rather foster sneaky protectionism under the guise of free trade. For this, the paper proposes an ideal-type free trade agreement benchmark model based on a classical liberal perspective and applies it in a multiple case study approach to assess three cases of recently concluded mega-RTAs: the Comprehensive and Progressive Trans-Pacific Partnership (CPTPP), the renegotiated North American trade agreement USCMA, and the Canada-European Union (EU) agreement CETA. The article shows that all of them are far from the classical liberal ideal of totally free trade and have a high content of back door protectionism suitable to raise trade barriers when politically opportune. In particular, the United States-Mexico-Canada Agreement (USMCA) includes many clear protectionist provisions that might even outweigh its liberalizing stipulations, whereas CPTPP and CETA can be deemed net liberalizing. It concludes that given political economy constraints, RTAs can nevertheless remain a second-best solution to the classical liberal ideals of completely unhampered trade and unilateral liberalization provided that they remove more impediments to free exchange than they cement or create.
Keywords: B12; B27; F02; F13; F55; 650; free trade; trade agreements; protectionism; classical liberalism; political economy